Entrepreneurship and human capital development in children - Kasper Brandt; Longinus Rutasitara; Onesmo Selejio; Neda Trifkovic (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper explores the link between entrepreneurship and child human capital development. We specifically examine how operating a non-farm enterprise (NFE) as opposed to working in agriculture relates to child labour and schooling outcomes. Accounting for timeinvariant unobservable characteristics in an estimation with individual fixed effects, we find a negative correlation between NFE ownership and child labour, especially in households with relatively higher levels of consumption expenditure. We find differentiated impacts by child gender and the type of enterprise: a lower incidence of child labour for boys and NFEs without employees and a lower incidence of child labour for girls and NFEs that hire at least one employee. Fatherowned NFEs correlate negatively with child labour for boys, both at the extensive and at the intensive margin, and positively with a higher likelihood for school attendance for girls. Given these findings, it appears that household entrepreneurship may contribute to decreasing the severe child labour problem in Tanzania, but resolving the problem of low school attendance rates will require a different strategy.
Keywords: M21; I25; J20; J24; J46; 330; non-farm; enterprise; child labour; schooling; Tanzania